The Effect of Firm Size, Leverage, and Profitability on the Integrity of Financial Reports in Banking Sector Companies Listed on the IDX in 2022-2024 - Delinda, Niken Rara; Aminah, Aminah (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the influence of firm size, leverage, and profitability on financial report integrity in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Financial report integrity is a crucial aspect in the banking sector given its role in maintaining public trust and financial system stability. This study employed a quantitative approach using library research and documentation techniques. The data used were secondary data sourced from the annual financial reports of banking companies. The research sample was determined using a purposive sampling technique with specific criteria, resulting in 29 banking companies with a total of 87 observations. After conducting an outlier test, four data points were excluded, resulting in a final data analysis of 83 observations. Data analysis was performed using multiple linear regression with SPSS software after meeting the classical assumption test and performing residual correction transformations to improve the quality of the model estimation. The results show that firm size has a positive effect on financial statement integrity, while leverage and profitability have a negative effect. These findings indicate that firm size encourages increased transparency and accountability, while debt pressure and the drive to maintain profit performance have the potential to undermine financial reporting integrity. This research is expected to provide empirical contributions to the development of accounting literature and provide considerations for management, investors, and regulators in improving the quality and integrity of banking financial reports.